2001
DOI: 10.1254/jjp.87.297
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Learning and Memory Impairment Induced by ⊿9-Tetrahydrocannabinol in Rats

Abstract: ABSTRACT-We investigated the characteristics of D 9 -tetrahydrocannabinol (THC)-induced impairment of learning and memory using an 8-arm radial maze task, a water maze, a visual discrimination task with 2 figures and a passive avoidance test in rats. THC (6 mg /kg, i.p.) impaired spatial memory in the standard task of the 8-arm radial maze. THC (4 -6 mg /kg, i.p.) selectively impaired working memory in a reference and working memory task of the 8-arm radial maze. Even at a dose of 10 mg /kg, THC did not impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 33 publications
5
44
0
1
Order By: Relevance
“…Some evidence supports the idea that the natural and synthetic cannabinoids impair cognitive processes in humans, nonhuman primates, and rodents (Braida and Sala, 2000) and seem to inhibit hippocampal extracellular acetylcholine release (Terranova et al, 1996). Rimonabant reverses many of the biochemical physiological and behavioral effects of cannabinoid receptor agonists; e.g., it attenuates the memory impairment produced by AEA and THC (Mallet and Beninger, 1998;Mishima et al, 2001). Rimonabant, which per se does not influence memory processes at the dose of 0.5 mg/kg, completely antagonizes the impairment produced by the synthetic cannabinoid CP 55,940 (Braida and Sala, 2000).…”
Section: Other Effects Of Rimonabantmentioning
confidence: 84%
“…Some evidence supports the idea that the natural and synthetic cannabinoids impair cognitive processes in humans, nonhuman primates, and rodents (Braida and Sala, 2000) and seem to inhibit hippocampal extracellular acetylcholine release (Terranova et al, 1996). Rimonabant reverses many of the biochemical physiological and behavioral effects of cannabinoid receptor agonists; e.g., it attenuates the memory impairment produced by AEA and THC (Mallet and Beninger, 1998;Mishima et al, 2001). Rimonabant, which per se does not influence memory processes at the dose of 0.5 mg/kg, completely antagonizes the impairment produced by the synthetic cannabinoid CP 55,940 (Braida and Sala, 2000).…”
Section: Other Effects Of Rimonabantmentioning
confidence: 84%
“…⌬ 9 -THC and related chemicals, known as cannabinoids, produce their psychoactive effects by acting at the cannabinoid-1 (CB 1 ) receptor in brain areas associated with learning and memory and elsewhere (Herkenham, 1991). Particular interest has focused on the effects of cannabis on cognition, because both naturally occurring and synthetically derived cannabinoids disrupt performance in a variety of rodent spatial (Lichtman et al, 1995;Lichtman and Martin, 1996;Mishima et al, 2001;Nava et al, 2001) and operant (Heyser et al, 1993;Hampson and Deadwyler, 1999) models of learning and memory.…”
Section: N-(piperidin-1-yl)-5-(4-chlorophenyl)-1-(24-dichlorophenyl)-mentioning
confidence: 99%
“…The Morris water maze has been a particularly useful tool to investigate both the physiological function of the endocannabinoid system (Varvel and Lichtman, 2002;Varvel et al, 2005a) and the impact of exogenous cannabinoid administration on learning and memory (Mishima et al, 2001;Varvel et al, 2001). Repeated injections of either ⌬ 9 -THC (da Silva and Takahashi, 2002) or the potent cannabinoid receptor agonist HU-210 (Ferrari et al, 1999) before each acquisition session have been shown to disrupt the ability of rodents to learn the location of a hidden platform that remains in a fixed location.…”
Section: N-(piperidin-1-yl)-5-(4-chlorophenyl)-1-(24-dichlorophenyl)-mentioning
confidence: 99%
“…All paired comparisons performed with Tukey procedure. (Castellano et al 1997(Castellano et al , 2003Mishima et al 2001;Niyuhire et al 2007). This suggests that indirect cannabinergic effects of URB597 (i.e., increased anandamide levels) could produce a learning impairment.…”
mentioning
confidence: 99%